PENGARUH LIKUIDITAS, STRUKTUR ASET, KEPEMILIKAN MANAJERIAL TERHADAP STRUKTUR MODAL DENGAN TINGKAT PERTUMBUHAN SEBAGAI MODERASI - Ramadhan, Muhammad Rifqi; Mayangsari, Sekar (APSSAI, 2022)
This study aims to examine the impact of liquidity, asset structure, and managerial ownership on capital structure with growth rate as a moderating variable. This empirical analysis is based on secondary data on manufacturing businesses listed on the Indonesia Stock Exchange. Purposive sampling was used, resulting in as many as 74 firms being acquired. Data sources were acquired from www.idx.co.id and the observation period 2018-2020. According to the findings of this study, liquidity and management ownership have a negative correlation with capital structure, and Asset Structure does not correlate with capital structure. Moreover, the growth rate mitigates the negative correlation between liquidity on capital structure. The growth rate does not enhance the positive correlation between asset structure on capital structure and does not mitigate the negative correlation between managerial ownership on capital structure.